Gender disparities in brain tumours: A Pakistan brain tumour epidemiology study analysis - Mashal Murad Shah; Muhammad Usman Khalid; Mohammad Hamza Bajwa; Farhan A Mirza; Saad bin Anis; Naveed Zaman Akhunzada; Altaf Ali Laghari; Muhammad Faraz Raghib; Sameen Siddiqi; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
Objective: To explore the differences in demographic, surgical, and prognostic characteristics between the two genders in patients with brain tumours in Pakistan. Methods: This study was a retrospective cross-sectional analysis of patients with a histopathological brain tumour diagnosis across 32 high-volume hospitals in Pakistan. The study period was from January 1, 2019, to December 31, 2019. There were no restrictions on inclusion apart from time. Results: From 2750 patients enrolled in the study, 1605 (58.4%) were male, and 1142 (41.6%) were female . The median age amongst males was 36 (24-49), while the median age amongst females was 37 (24-48). The ratio of married to unmarried patients was 2.7:1 for females and 1.3:1 for males. Surgical treatment was carried out for 1430 (58.1%) males and 1013 (41.9%) females. The median time to surgery was 25 (4-107) days for males and 31 (5-98) days for females. The greatest disparity in tumour malignancy was in grade IV gliomas. Conclusion: Males generally have a higher incidence of brain tumours in our experience, apart from meningiomas, which favour females. The mortality rate and glioblastoma incidence rate are both higher amongst males. However, post-treatment cure is also witnessed. Sociocultural norms play a prominent role in accessing healthcare. Women are generally at a disadvantage compared to their male counterparts, which may impact reporting of brain tumour cases and treatment outcomes. Keywords: Brain neoplasms, Epidemiology, Gender equity, Retrospective study. Continue....